Inovasi Pembelajaran Bahasa Indonesia Berbasis Deep Learning dengan Model Cooperative Learning melalui Kegiatan Membaca Bermakna - Chandra Langening Tyas; Detania Qudratul Aulia; Farid Putra Apriyanto; Panca Dewi Purwati (ALSYS, 2026)
Although meaningful reading skills have received considerable attention in research on early literacy development, studies that specifically integrate the principles of Deep Learning with Cooperative Learning to enhance meaningful reading among lower-grade students remain limited. This study aims to evaluate the effectiveness of an instructional innovation in Bahasa Indonesia that integrates Deep Learning and Cooperative Learning to improve meaningful reading skills among first-grade students. A mixed-methods approach was employed using a modified Research and Development (R&D) design, involving 18 students selected through purposive sampling. Data were collected through classroom observations, field notes, teacher interviews, and pretest–posttest assessments of reading skills, and were analyzed using descriptive statistics and thematic analysis. The findings indicate a significant improvement in students’ meaningful reading ability, reflected in enhanced comprehension of text content, active participation, collaborative attitudes, and reflective engagement during learning activities, although a small number of students still required additional support in recognizing simple words, indicating differing levels of learning readiness. Theoretically, the study reinforces the relevance of Deep Learning principles—mindful, meaningful, and joyful learning—in the development of early literacy, while practically it produces a teaching module that teachers can use to strengthen Bahasa Indonesia instruction in the early grades. It is concluded that the integration of Deep Learning and Cooperative Learning plays an important role in fostering meaningful reading skills and collaborative character from the primary school level, and further research is recommended to test this instructional model in other subjects and grade levels to broaden the generalizability of the findings.